PENERAPAN METODE ACTIVITY BASED MANAGEMENT TERHADAP PENINGKATAN PENJUALAN PADA RESTORAN BEBEK UBUD - Husna, Asmaul; Dwilita, Handriyani (CV. Lafadz Jaya, 2024)
Activity-based management (ABM) is a method of managing activities to increase customer value and generate profits. ABM is a concept where you need to know whether a company is using its resources or not. This research aims to determine the application of activity-based management (ABM) in the Wong Solo grilled chicken business. The type of research carried out by the author in this research is qualitative with a strict case study. The data analysis process includes data reduction, data presentation, drawing conclusions or verification. The research results show that three activities that do not provide added value can be eliminated or combined with other or previous activities. In this case we assume the daily production cost is Rp. 2,000,000 x 7.5% water requirements = IDR 150,000.-. So, you can save water needs (electricity costs due to groundwater use) with just one process of IDR 150,000,-.